Election reporting and githerinization of Kenya's media. (1st September 2020) - Ugangu, Wilson
Kenya's media landscape has greatly transformed since the reforms of the 1990s, resulting in increased private ownership of media. The relationship between the media, politics and the citizen has been the most affected by these transformations. Using examples from Kenya's 2017 elections, this article attempts to show how this relationship has changed and the opportunities and challenges for modern political communication. This article argues that although new trends in political communication have resulted in complex and dynamic political campaigns, they have also resulted in the atomization and alienation of the citizen in the democratic enterprise. This analysis is made against the backdrop of the political economy of the media theoretical perspective and, to an extent, emerging literature on media and globalization and attendant forces on the Kenyan society in general.